Philosophical Analysis of the Concept of Faith on the Basis of Benedict XVIʼs Encyclicals - Marcin Sieńkowski (Wrocławski Przegląd Teologiczny)
The article deals with the problem of faith based on three encyclicals of Benedict XVI. The author pays attention to what and how the pope says about faith from the point of view of philosophical analysis (realistic trend). It is important to show the essence, purpose and structure of the act of faith. The conducted study allows us to conclude that Benedict XVI defends the claim that supernatural faith is the substance (basis) of invisible things (Letter to the Hebrews). Thanks to it, it becomes possible to present the goal in the form of eternal (happy) life. Its updated demands the involvement of intellect and will in an act of faith. In this way, the pope emphasizes that faith is constituted by both purposeful and subjective reasons (the structure of faith). The philosophical analysis of the concept of faith presented in the article is not only about quoting the position of Benedict XVI, but also about recalling the views of those thinkers (Bacon, Luther, Kant) with whom the pope argues.